Rethinking the Democratic Participant Media Theory for African Development and Good Governance: Issues and Perspectives from Nigeria - Ifeanyi Martins Nwokeocha (Al-Makki Publisher, 2025)
This research examines the role of the Democratic-Participant Media Theory (DPMT) in promoting development and good governance in Africa, with a specific focus on Nigeria. Employing a qualitative analytical research approach, the study builds on an extensive review of literature from scholarly journals, books, and institutional reports. The findings indicate that African nations, particularly Nigeria, continue to grapple with political instability and underdevelopment, partly due to the ineffective application of imported Western democratic models and media frameworks. Denis McQuail's Democratic-Participant Media Theory is presented as a viable alternative that emphasizes grassroots participation, access to media, and the democratization of communication. The theory supports the use of media—including small-scale and local outlets—to enhance civic engagement, hold government accountable, and foster inclusive development. This study concludes that adopting DPMT can strengthen democratic processes, amplify citizen voices, and contribute to sustainable governance and development in Africa. It urges African leaders and policymakers to leverage media pluralism and participatory communication to achieve lasting political and socioeconomic progress.